Cationic porphyrin–xylan conjugate hydrogels for photodynamic antimicrobial chemotherapy. Issue 38 (9th June 2022) - Elkihel, Abdechakour; Vernisse, Charlotte; Ouk, Tan‐Sothéa; Lucas, Romain; Chaleix, Vincent; Sol, Vincent
Abstract: Bio‐based hydrogels are attractive materials for many biomedical purposes such as drug delivery or wound healing. A light‐triggered antibacterial activity can be conferred to hydrogels after their conjugation to appropriate photosensitizers (PS). In this study, we have synthesized and characterized hydrogels consisting of cationic porphyrin–xylan conjugates. A cationic porphyrin was covalently attached to xylan by an esterification reaction. Different porphyrin‐xylan derivatives were obtained with degrees of substitution ranging from 0.003 to 0.053. Then, the derivatives were cross‐linked after reaction with diethylenetriaminepentaacetic (DTPA) dianhydride to obtain the corresponding hydrogels. The study of the morphology and rheology of the hydrogels showed that the materials obtained present interconnected porous structures, good mechanical integrities as well as high swelling ratios. Antimicrobial activity of cationic porphyrin–xylan conjugate hydrogels was tested under white light irradiation against Staphylococcus aureus and Pseudomonas aeruginosa . All of the tested hydrogels showed photo‐bactericidal activity against the two tested strains. Abstract :